implementation of a zip function that takes two lists as parameters and returns a new list of pairs. I got this so far
myZip [] [] = []
myZip (x:xs) (y:ys) = [(x,y)] ++ myZip xs ys
any help?
There's really only one way to write it for lists, even for homework:
zip :: [a] -> [b] -> [(a,b)]
zip (a:as) (b:bs) = (a,b) : zip as bs
zip _ _ = []
or, more generally,
zipWith :: (a -> b -> c) -> [a]->[b]->[c]
zipWith f (a:as) (b:bs) = f a b : zipWith f as bs
zipWith _ _ _ = []
If you want to get wacky, and play with stream fusion, the version from the stream fusion paper, in automaton style,
zipWith :: (a -> b -> c) -> Stream a -> Stream b -> Stream c
zipWith f (Stream next0 sa0) (Stream next1 sb0) = Stream next (sa0, sb0, Nothing)
where
next (sa, sb, Nothing) = case next0 sa of
Done -> Done
Skip sa' -> Skip (sa', sb, Nothing)
Yield a sa' -> Skip (sa', sb, Just a)
next (sa', sb, Just a) = case next1 sb of
Done -> Done
Skip sb' -> Skip (sa', sb', Just a)
Yield b sb' -> Yield (f a b) (sa', sb', Nothing)